From Aroma Chemistry via Bioactives to Toxicology – Remembering the Broad Expertise of Michael Granvogl in Food Science - Jonathan Beauchamp; Yu Wang; Xiaoting Zhai (Journal of Food Bioactives, 2023)
On March 23, 2022, the field of food science lost a pioneering and impassioned scientist through the tragic and untimely passing of Prof. Michael Granvogl. Born on December 21, 1974 in Munich, Germany Michael’s inquisitive nature led him to study food chemistry at the Technical University of Munich (TUM). After graduating in 1998, he remained at TUM to pursue a doctoral degree (conferred in 2007), then habilitation (2016), qualifying him as Associate Professor in Food Chemistry. In 2019, Michael Granvogl was appointed Full Professor at the Institute of Food Chemistry, University of Hohenheim, Germany where he managed a young and dynamic team of enthusiastic scientists in their pursuits to push the boundaries of food chemistry research in their specialized disciplines. Indeed, Michael was a renowned international subject-matter expert on multiple facets of food chemistry, foremost on aroma-active compounds and food-borne toxicants, with a deep knowledge of their formation and degradation mechanisms, and with skilled application of effective extraction procedures and comprehensive analytical techniques to explore and elucidate their nature. Beyond his teaching and research, Michael was a staunch and dedicated member of the Division of Agricultural and Food Chemistry (AGFD) of the American Chemical Society (ACS), taking active and prominent roles on the executive committee to promote the field and support the next generation of scientists. As a native of the city of Munich, it might be noted that his passion for science, evidenced in lecture theaters and laboratories, was mirrored in his private life through his enthused and loyal support of his native soccer team, FC Bayern Munich. That team must now move forward with the loss of one dedicated fan, but the field of food chemistry – in particular the sub-discipline food bioactives – must overcome the void previously filled with Michael Granvogl’s stalwart presence and must cope with the absence of discoveries that will no longer materialize. There are many researchers in the field who lost a dedicated mentor, an esteemed colleague and a dear friend on that fateful day in spring 2022.